Byblos in the Third Millennium B.C. A Reconstruction of the Stratigraphy and a Study of the Cultural Connections - Saghieh, Muntaha (1983)
£32.00/$69.00; distributed in North America by Humanities Press, Inc., Atlantic Highlands, New Jersey 07716.